STRATEGI PENGEMBANGAN SANCTUARY RUSA TIMOR (Rusa timorensis) TAMAN WISATA ALAM GUNUNG TUNAK, LOMBOK TENGAH - Lutfia Azizah; Agum Muladi (Universitas Pakuan, 2022)
Taman Wisata Alam Gunung Tunak is a conservation area located in Central Lombok Regency. One of the tourist attractions that can be developed in TWA Gunung Tunak is the Timor Deer Sanctuary (Rusa timorensis). To be developed into a tourist attraction, a study was conducted that aimed to develop a timor deer sanctuary at TWA Gunung Tunak. The method used is through observations carried out directly in the field and interviews with 2 management units managing the area and analyzed using a SWOT (Strength, Weakness, Opportunities, Threats) analysis. The results showed that the recommendation strategy, namely First, the S-O strategy of 2.5 by optimizing and increasing cooperation and utilizing the budget according to the planning that has been prepared. Second, the S T strategy of 2.2 by optimizing and utilizing the budget in sanctuary management by improving facilities and infrastructure. Third, the W-O strategy of 1.66 by optimizing coordination and planning budgets for sanctuary management needs. Finally, the W-T strategy of 1.36 by increasing and planning for the management needs of timor deer in improving sanctuary commodities. So it can be concluded that the priority strategy that can be used in developing the TWA Gunung Tunak timor deer sanctuary is the S-O strategy with a value of 2.50. The strategy carried out is to optimize and increase cooperation and utilize the budget according to the planning that has been prepared to maximize the implementation and development of the timor deer sanctuary.